Dukungan Sosial Teman Sebaya dan Self-regulated learning pada Mahasiswa Perantau - Fitria, Ana; Rahma, Elfia Afifah; Aini, Dewi Khurun (PSIMPHONI, 2024)
This study aims to determine the relationship between self-regulated learning and peer social support in migrant students at UIN Walisongo. The research method used is quantitative correlation with analysis using Pearson correlation. The instruments used include peer social support and self-regulated learning scales. The research sample was taken using purposive sampling method involving 128 subjects. The results showed a positive relationship between peer social support and self-regulated learning in migrant students at UIN Walisongo. It can be concluded that the higher the social support of peers, the higher the ability of self-regulated learning in migrant students.